Pengaruh Pelatihan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan UPTD Puskesmas Pagu - Nauvan Dwi Ferdian Penulis; Iing Sri Hardiningrum; Anita Sumelvia Dewi (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
The problem in the object of research is the lack of effectiveness of job training in the field of technology, while in work discipline there are still employees who do not carry out discipline on time or are late in working. This thesis aims to prove the hypothesis of the researcher: there is a partial influence of Job Training (X1), Work Discipline (X2), on employee performance (Y). This study used quantitative methods with multiple linear regression analysis techniques. This research data was obtained by interview, observation, literature study, and questionnaire methods. The sample return in this study used a saturated sampling technique, namely all employees of UPTD Company. Puskesmas Pagu as many as 32 people. The results of the study using the help of SPSS program proposal version 25, showed that: (1) job training has a partial but not significant effect on employee performance with a calculated value of -1.381 and a value of Sig. 0.178 > 0.05. (2) and work discipline partially affects employee performance with a calculated value of 3.795 and a value of Sig.0.001 < 0.05 (3) job training, and work discipline simultaneously has a significant effect on employee performance with a value of Fcalculate 13.489 and a value of Sig. 0.003 < 0.05. From the test results of multiple linear regression analysis, it produces the equation formula Y = 13.489 + -1.381 X1 + (3.795X2) + e.